Perancangan Dan Analisis Kinerja ProgramKrs Berbasis Java Client Server - Ajie Pradana, Dhandy; , Husni Thamrin, S.T, MT., Ph.D; , Tindyo Prasetyo, S.T (2016)
KRS is a term reserved for the course registration process that must be done by the students. In the process of KRS student must choose courses that will be taken, along with the classes and schedule based on the list of courses with schedules and classes are opened. The first stage is to collect data used for the manufacture of these applications, java programming books as well as from the Internet or library for additional programming. This application uses the Java programming language with a development tool NetBeans 7.0 and MySQL. Further assessment will be taken as a result of KRS-based java client application server. The application consists of several Form that is Form login, Biodata Form, Form Menu_utama, Form Tambah_matakuliah, Kuliah_semester_pendek Form, and Form Ganti_Password. The results of this application in terms of speed KRS Java-based client server more quickly because the database is stored in the manufacturing and testing localhost still one by one. And in terms of web-based online KRS see so much nicer.